2015
DOI: 10.1016/j.ygeno.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq identifies novel myocardial gene expression signatures of heart failure

Abstract: Heart failure is a complex clinical syndrome and has become the most common reason for adult hospitalization in developed countries. Two subtypes of heart failure, ischemic heart disease (ISCH) and dilated cardiomyopathy (DCM), have been studied using microarray platforms. However, microarray has limited resolution. Here we applied RNA sequencing (RNA-Seq) to identify gene signatures for heart failure from six individuals, including three controls, one ISCH and two DCM patients. Using genes identified from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
210
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(219 citation statements)
references
References 29 publications
7
210
0
2
Order By: Relevance
“…1C). In line with our findings, a recent RNA-sequencing study of samples from failing human hearts reported increased PDE1C expression in both ischemic heart disease and dilated cardiomyopathy (15).…”
Section: Pde1c Expression In Failing Heartssupporting
confidence: 92%
“…1C). In line with our findings, a recent RNA-sequencing study of samples from failing human hearts reported increased PDE1C expression in both ischemic heart disease and dilated cardiomyopathy (15).…”
Section: Pde1c Expression In Failing Heartssupporting
confidence: 92%
“…Three (influenza infection, bacterial sepsis and pulmonary tuberculosis) were used as previously described (1821), and three new analyses were constructed according to criteria below (cardiomyopathy (4455), kidney transplant rejection (14,5667) and lung adenocarcinoma (6881), Supplementary Tables S1–S3). The three new analyses were arrived at by repeatedly performing systematic searches of NIH GEO and ArrayExpress for clinical ( in vivo ) studies that (i) yielded an aggregate sample size of >1000 samples from >10 datasets, (ii) measured the same disease state and had the same type of controls in each dataset and (iii) had appropriate study design (excluding studies where, for instance, healthy controls came from one batch and diseased samples were processed separately).…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of RCM versus NDR (controls) yielded 760 differentially expressed genes with at least a 1.5 fold difference and moderated t-test p < 0.05. To further control for possible differences in age or cardiac sample site, we analyzed previously described datasets profiling non-diseased human left and right ventricles (GSE57338 and GSE36761; See Table 3 for description of all datasets)910. We identified only a small number of genes anti-correlated with age (n = 10), none of which were increased in RCM (GSE57338).…”
Section: Resultsmentioning
confidence: 99%